The Loss of Ecological Control, Pastoralist Migration and Indigenous Knowledge in Tanzania - Awinia, Christopher S. (Tanzania Journal for Population studies and Development, 2023)
This article is based on a study on the implications of climate change in bringing about loss of ecological control and climate induced, forced pastoralist migration from one ecosystemic basin to another. It brings out a discussion that migration between different ecosystems lead to the inevitable loss of location-specific indigenous knowledge. This in turn contributes to loss of epidemic control which lead to increased livestock and human vulnerabilities in the destination areas. The article is based on empirical evidence demonstrating that pastoralists are increasingly becoming a vulnerable population group, and internally displaced to new ecosystems as a result of migration as a coping mechanism from extreme weather variations. The study was guided by three objectives: a) to determine whether such migration trends are induced by climate change and loss of ecological control; b) to determine recent trends of pastoralist and livestock migration in Tanzania, and c) to determine the implication of pastoralist migration and loss of indigenous knowledge. The article is based on a study that interviewed 544 pastoralist households in seven districts in Tanzania. A total of 54 Focus Group Discussions and 17 Key Informant Interviews were conducted to complement the household survey. The study provided evidence derived from case-study areas in which recent climatic changes and extreme weather conditions have had accelerated loss of ecological control leading to forced out- migration, depletion of location specific indigenous knowledge and increased vulnerability to epidemics. The article concludes that loss of ecological control is closely associated with loss of epidemic control.